TESOL teacher education a reflective approach - Farrell, Thomas S. C. ca. 20./21. Jh (Edinburgh textbooks in TESOL, 2021)
"A 200 hour teacher education program, often heavily focused on theory and where practice is left to short field experiences cannot provide you with everything that you will need when working in a real classroom. In this book Thomas Farrell addresses two problems within TESOL teacher education – the perceived gap between theory and practice and the lack of contact with newly qualified teachers. Farrell outlines how to prepare for the realities of what you will face when beginning your career through reflective activities that include: case-based teaching, teaching metaphor analysis, critical incident analysis, and teacher identity analysis. Including data-based vignettes from diverse contexts of language teachers, you are able to gain practical insights from language teacher education courses. Whether a learner teacher or teacher educator, this book presents new insights into the reality of TESOL teacher education."